Grain Growth during Annealing of Ultrafine-Grained and Nanomaterials - I.E. Volokitina, T.D. Fedorova, and D.N. Lavrinyuk (Успехи физики металлов)
Ultrafine-grained metals and alloys with a submicrocrystalline structure in some cases demonstrate a set of unique properties, for example, high strength and hardness, low-temperature superplasticity at high strain rates, and improved electrical and magnetic properties. Severe plastic deformation (SPD) is one of the main methods for producing ultrafine-grained materials, and various methods of SPD have been developed in recent decades. The uniqueness of these methods is the ability to deform the material to large degrees of deformation without significantly changing the external dimensions of the product; that is, strain by methods of SPD is mainly aimed at changing the internal structure of materials, namely, the dimensions of structural elements. Along with the ultrafine structure, the most important feature of ultrafine-grained materials obtained by SPD is the presence of deformation-modified (‘nonequilibrium’) crystallite boundaries. In recent years, considerable attention has been paid to the study of nonequilibrium grain boundaries. However, as a rule, such studies were carried out using one research method (electron microscopy, determination of diffusion parameters, tunnelling or atomic force microscopy, etc.), which did not allow a comprehensive characterisation of the state of grain boundaries. Therefore, there is a need for a comprehensive study of the state of grain boundaries in ultrafine-grained materials subjected to SPD.